2006
DOI: 10.3168/jds.s0022-0302(06)72526-7
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in Swedish Dairy Calves and Replacement Heifers

Abstract: The mortality of 8,964 heifer calves born in 122 dairy herds in southwest Sweden in 1998 to 2000 was monitored from January 1998 until December 2000. Farmers were requested to send carcasses for necropsy from animals that died from 1 d of age to first calving. Age and seasonal patterns of mortality were investigated using Kaplan-Meier curves. The median herd-level mortality risk was 2.1%. In total, 3.1% of the animals died before 90 d of age, 0.9% between d 91 and 210, and 2.2% between d 211 and first calving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
108
4
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(140 citation statements)
references
References 24 publications
19
108
4
9
Order By: Relevance
“…The larger 19 farm study similarly found that 17 out of 489 calves present at 6 months of age had died or had been culled by 15 months (3.5%). Our data support Svensson et al (2006) in concluding that accidents were the main cause of mortality in this age group.…”
Section: Neonatalsupporting
confidence: 87%
See 1 more Smart Citation
“…The larger 19 farm study similarly found that 17 out of 489 calves present at 6 months of age had died or had been culled by 15 months (3.5%). Our data support Svensson et al (2006) in concluding that accidents were the main cause of mortality in this age group.…”
Section: Neonatalsupporting
confidence: 87%
“…Large offspring, maternal overfatness and milk fever can also cause dystocia. Other risk factors for mortality include sire, gestation length, calf gender, twinning, season of birth, herd size and adequacy of calving supervision (Svensson et al, 2006).…”
Section: Perinatalmentioning
confidence: 99%
“…It appeared that many risk factors for calf morbidity reported in literature are linked to the housing systems described in this study. Housing systems have also been reported to have an effect on mortality (Svensson et al, 2006b;Gulliksen et al, 2009c). Risk factors are associated to characteristics of housing systems that vary a lot in our study, particularly when it comes to collective rearing at young age.…”
Section: Discussionmentioning
confidence: 65%
“…The search terms were: bovine respiratory disorders, bovine respiratory diseases, bovine respiratory disease complex and/ or neonatal diarrhoea, enteric infectious diseases and dairy calf/calves combined with risk factors. Information relative to hygiene practices (removing litter, disinfection, straw quantity) and air conditioning while being recognised as main risk factors for calf diseases (Svensson et al, 2003 and2006b;Lago et al, 2006) were not investigated through the questionnaire because these practices and data are very different between farms even within the same calf housing system. Finally, a qualitative risk assessment of the different reported calf housing systems for neonatal diarrhoea and BRD complex was performed.…”
Section: Questionnaire Designmentioning
confidence: 99%
“…Herd-level risk factors e.g herd size, region, predominant breed in the herd, herd milk yield, grazing, proportion of purchased animals have shown to influence dairy cow mortality Burow et al, 2011;Raboisson et al, 2011;Alvåsen et al, 2012). Some examples of animal level risk factors associated with calf and youngstock mortality are breed, gestation length, parity of the dam, dystocia, being born as a twin or triplet, congenital defects, calving season, sex and weight of the calf, respiratory disease, diarrhea and arthritis (Svensson et al, 2006;Gulliksen et al, 2009;Bleul, 2011;Raboisson et al, 2013). Few examples of herd-level risk factors for calf mortality are herd size, characteristics of calving stall, suckling as feeding regimen and housing system from 2 weeks of age (Gulliksen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%